The Effect of Economic Growth in Terms of Expenditure on Poverty in Indonesia - Sudradjat, Cindy Melania V; Arham, Muhammad Amir; Akib, Fitri Hadi Yulia; Santoso, Ivan Rahmat (Jurnal Penelitian Ekonomi Dan Akuntansi, 2024)
This study aims to analyze the effect of economic growth in terms of expenditure on poverty in Indonesia. The data used in this study is secondary data sourced from the Central Statistics Agency, which was obtained from 34 provinces in Indonesia. This study used Multiple Linear Regression Analysis Panel data using Fixed Effect Model (FEM). The results of this study show that 1) Household consumption expenditure has a positive and insignificant effect on poverty in Indonesia; 2) Gross fixed capital formation has a negative and significant effect on poverty in Indonesia; 3). Government consumption expenditure has a positive and significant effect on poverty in Indonesia; 4). Net exports have a positive and significant effect on poverty in Indonesia.